Submission of VO #12 - Valuation for dam proofing works in Raft, Pile cap, H-steel and King post (Rev. v3) - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding submission of VO #12 - valuation for dam proofing works in Raft, Pile cap, H-steel and King post (Rev. v3) of BRAC University new campus project.